2020
DOI: 10.1073/pnas.2007213117
|View full text |Cite
|
Sign up to set email alerts
|

Designed nanomolar small-molecule inhibitors of Ena/VASP EVH1 interaction impair invasion and extravasation of breast cancer cells

Abstract: Battling metastasis through inhibition of cell motility is considered a promising approach to support cancer therapies. In this context, Ena/VASP-depending signaling pathways, in particular interactions with their EVH1 domains, are promising targets for pharmaceutical intervention. However, protein–protein interactions involving proline-rich segments are notoriously difficult to address by small molecules. Hence, structure-based design efforts in combination with the chemical synthesis of additional molecular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 60 publications
3
49
0
Order By: Relevance
“…Zyxin, which contains four clustered FP4 motifs, has been shown to bind to the VASP EVH1 domain by contacting both the canonical FP4 site and a noncanonical site on the opposite side of the EVH1 domain (Acevedo et al, 2017). Interestingly, a crystal structure of the ENAH EVH1 domain bound to a single-FP4 motif peptide at the canonical site also contains a second single-FP4 peptide bound to the region corresponding to the noncanonical binding site in VASP (PDB 5NC7, Barone, 2020). To test whether multi-FP4 peptides engage this noncanonical site, we designed ENAH EVH1 R47A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zyxin, which contains four clustered FP4 motifs, has been shown to bind to the VASP EVH1 domain by contacting both the canonical FP4 site and a noncanonical site on the opposite side of the EVH1 domain (Acevedo et al, 2017). Interestingly, a crystal structure of the ENAH EVH1 domain bound to a single-FP4 motif peptide at the canonical site also contains a second single-FP4 peptide bound to the region corresponding to the noncanonical binding site in VASP (PDB 5NC7, Barone, 2020). To test whether multi-FP4 peptides engage this noncanonical site, we designed ENAH EVH1 R47A.…”
Section: Resultsmentioning
confidence: 99%
“…Barone, et al have shown that small-molecule Ena/VASP EVH1 domain inhibitors reduce breast cancer-mediated invasion in zebrafish models, and in in vitro invasion assays, establishing Ena/VASP EVH1 domains as promising therapeutic targets (21). Yet Ena/VASP paralogs have distinct functions in cancer.…”
Section: Engineered Enah Ligands Are Tools To Probe Enah-specific Biomentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is not surprising that Fe65, APP, Mena, cortactin, and ELMO/DOCK180/Rac are involved in suppressing or supporting different kinds of cancerous signaling cascades, for example, in breast, thyroid, colon, lung, and pancreas cancer [ 56 , 128 , 185 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. It was astonishing that especially breast cancer was highly investigated in association with Fe65 interaction partners (APP, Mena, cortactin, ELMO/DOCK180/Rac) separately but not in a common pathway [ 56 , 187 , 188 , 189 , 190 , 191 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ].…”
Section: Genetic Evidence For Fe65 Function In Actin Cytoskeleton Regulationmentioning
confidence: 99%
“…Aiming at the synthesis of the dipeptide mimetic ProM‐17 ( 9 ) [5c] we recognized that the developed amination protocol afforded the required amine building block, i. e. the N‐allylated glycine ester 10 a , only with unsatisfying enantioselectivity (80 % ee ) under the established conditions using L3* (Scheme 3; Table 1).…”
Section: Introductionmentioning
confidence: 99%